EPISTEMIC BELIEFS ON FIELD-DEPENDENT AND FIELD-INDEPENDENT LEARNING STYLE - M Nur Ghufron; Rini Risnawita Suminta (Jurnal Cakrawala Pendidikan, 2020)
Research in contemporary education over the past few decades has led to considering the influence of non-cognitive factors such as learning styles in various learning behaviors. This study aims to examine the influence of the epistemic beliefs that consist of belief in knowledge and belief in learning on field-dependent and field-independent learning styles. The sample consisted of 129 students at the Early Childhood Islamic Education Study Program, Department of Islamic Education, Kudus State Islamic Institute through the simple random sampling technique. The data collection technique was through the use of questionnaires. There are three scales employed in this study, namely epistemological trust scale, dependent learning style and independent learning style. Data were analyzed by using Structural Equation Modeling. The results show that the belief in learning has a significant and positive effect on the field-dependent and field-independent learning style. Meanwhile, the belief in learning has only a significant and negative effect on the field-independent learning style and has no significant effect on field-dependent learning style. The results provide some insightful considerations regarding the utilization of epistemic beliefs for improving learners’ interaction with the surrounding context to obtain an optimal academic performance.